ANALISIS KORELASI KOEFISIEN KONTINGENSI UNTUK MENGETAHUI BESARNYA HUBUNGAN KEJADIAN ISPA PADA REMAJA - Novrika Silalahi; Josua Partogi Rumahorbo (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2018)
The purpose of this study was to determine the factors that cause the occurrence of ISPA in adolescents associated with the physical environmental conditions of houses in Namolandur Village, Namorambe District, Deli Serdang Regency. This type of research uses analytical survey research with cross sectional survey design. The population in this study were adolescents aged 12-15 years and aged 16-18 years as many as 80 adolescents. This sampling technique uses simple random sampling. The instruments used were questionnaires and measurements of air humidity, area of ​​ventilation, type of floor of the house, density of housing, roof of the house, and the walls of the house. The data obtained were analyzed using multiple logistic regression analysis. The results of this study indicate that of the six physical environmental indicators of the population that have a relationship to the incidence of ISPA, namely ventilation (p = 0.008), occupancy density (p = 0.041), air humidity (p = 0.024) and roof of the house (p = 0.006). Ventilation variables have contingency coefficient (C) = 0.409, house floor variable contingency coefficient (C) = 0.250, contingency coefficient density variable (C) = 0.336, air humidity coefficient contingency coefficient (C) = 0.364, house wall variable contingency coefficient ( C) = 0.033, the roof variable is the contingency coefficient (C) = 0,250